GAMBARAN PERILAKU MENGKONSUMSI MAKANAN CEPAT SAJI PADA MAHASISWA FAKULTAS ILMU PENDIDIKAN DI UNIVERSITAS NEGERI MEDAN - Mhd Abdul Rajab Harahap; Putra Apriadi Siregar (Jurnal Kesehatan, 2023)
What is the description of consuming fast food to students of English education at Medan State University and the objectives to be achieved from conducting the research to find out the description of consuming fast food to students of English education at Medan State University. This type of research is a descriptive study with a quantitative design population in This study included all active students of the Faculty of Education at Medan State University. The number of samples studied were 25 men and women from the Faculty of Education at Medan State University. Based on the factors causing the behavior of consuming fast food among students of the Faculty of Education, there are various factors that influence their fast food consumption patterns. It can be described that of the 25 respondents who stated that their consumption of fast food was 76%, they consumed fast food because it was fast and practical, 68% because it tastes good, 64% eat fast food because the place is easy to reach and raises the individual's mood, 60% eat fast food because it is a fast food brand and the price and 52% eat fast food because the place is comfortable and clean. This is in line with Kritianti's research (2009) that most respondents stated that the reason they often consumed fast food was because they were lazy to eat at home (62.7%). Negeri Medan ", the following conclusions can be drawn: The level of knowledge of these students is very high about fast food and the dangers of fast food content for the body. The level of consumption of fast food among these students stated that all respondents had consumed fast food and the highest factor was that they consume fast food because it is fast and practical and there are also many other reasons as described above. Based on the results of the research and conclusions described above, some suggestions can be given as follows: For students of the Faculty of Education to better regulate their food consumption patterns on frequent consumption of fast food. This is to avoid the effects that arise from consuming fast food. For readers, it is hoped that this research can be a source of insight and knowledge about fast food.